Antibiotic lock solutions allow less systemic antibiotic exposure and less catheter malfunction without adversely affecting antimicrobial resistance patterns. Issue 1 (20th June 2012) - Onder, Ali Mirza; Billings, A. A.; Chandar, Jayanthi; Nield, Linda; Francoeur, Denise; Simon, Nancy; Abitbol, Carolyn; Zilleruelo, Gaston
Abstract: There are current concerns that antibiotic lock solutions (ABL) can induce antimicrobial resistance in long‐term hemodialysis patients. Retrospective chart review of 157 children on hemodialysis between January 1997 and June 2006 was performed. In ERA I, only systemic antibiotics were used. In ERA II, ABL were added to systemic antibiotics when needed. In ERA III, ABL were used for treatment of all cases of catheter‐related bacteremia (CRB) and for CRB prophylaxis in high‐risk patients. The study includes 111, 325 catheter days. The CRB incidence was 3.9 CRB/1000 catheter days. There was significant decrease for the total systemic antibiotic exposure (P = 0.0484) and the percentage of catheters lost to malfunction (P = 0.001) in ERA III. Protocol ABL exposure was associated with a trend to increased tobramycin‐gentamicin resistance for gram‐positive CRBs (P = 0.2586) but with improved tobramycin‐gentamicin resistance for gram‐negative (P = 0.0949) and polymicrobial CRBs (P = 0.1776) and improved vancomycin resistance for gram‐positive CRBs (P = 0.0985). This retrospective analysis does not support the premise that ABL use will promote antimicrobial resistance in the hemodialysis population. The decreased exposure to systemic antibiotics by vigorous ABL use may even improve the antimicrobial resistance patterns in this population in the long term.